Curriculum renewal - Social studies - Beddoe, Innocent B. (Commonwealth Secretariat, 1974)
This paper aims at discussing the nature of social studies in education in the first instance, and at identifying current descriptions of social studies as an area of experience
Keywords: Curriculum development